Answer:
1- P(-0.47 < z < 0.47) = 0.63836
Step-by-step explanation:
Here, we want to get the answer to;
1-P ( -0.47 < z < 0.47)
Mathematically, we are going to use the standard normal distribution table for this
Let us try to evaluate;
P(-0.47 < z < 0.47)
Mathematically, that will be;
P (z < 0.47) - P(z < -0.47)
where P (z < -0.47) = P( z > 0.47)
so we have
P(-0.47 < z < 0.47) = P(z < 0.47) - P(z > 0.47)
So we have this using the standard normal distribution table as follows;
0.68082 - 0.31818 = 0.36164
Now, we can insert this in the earlier expression of;
1- P(-0.47 < z < 0.47)
= 1-0.36164 = 0.63836
Please give credit to Adetunmbiadekunle, who wrote this answer and do not mark me brainliest.